Optical Permittivity Of Aliphatic Alcohols, Polyethylene Glycols And Dye Solutions Using The Surface Plasmon Resonance Technique - Ikhsan, Nurul Izrini (2009)
Surface plasmon is a charge density wave that occurs at an interface between a thin metal film and dielectric medium. The most common means of excitation surface plasmon resonance is achieved through the Kretschmann configuration by utilizing the attenuated total reflection (ATR). In this study, gold with purity 99.99% was deposited onto glass cover slip in a form of thin film (thickness ~ 50 nm) using sputtering technique which then coupled onto one surface of 60° prism using index matching oil. Liquid samples used as the dielectric medium were aliphatic alcohols; (methanol, ethanol and 1-propanol), polyethylene glycols (PEG) series; (PEG 400, PEG 4000, PEG 1 0000 and PEG 20000) and dye solutions; (methylene blue, rhodamine B and rhodamine 6G). The intensity of the optical reflectivity was measured as a function of incident angle at the metal and dielectric interface.